Metal matrix composite grinding ball with structural reinforcement
By 3D printing, the ceramic hollow structural shell is manufactured and embedded in the ferroalloy metal matrix is solved, and the problem of difficult to take into account the wear resistance and corrosion resistance of existing abrasive balls under high mechanical stress and abrasive conditions is achieved, and the wear resistance of the abrasive balls is achieved Corrosion and impact resistance are improved and manufacturing costs are reduced.
Patent Information
- Application Number
- CN202380040154.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-01
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-24
AI Technical Summary
The existing grinding balls are difficult to have both abrasion resistance and corrosion resistance under high mechanical stress and abrasion conditions. The fine particles of ceramic particles are flammable and explosive, and have poor coarse performance, making it difficult to obtain a solid hollow structure through additive manufacturing. .
Using 3D printing technology to manufacture ceramic hollow structural shells, embedded in ferroalloy metal matrix, and using micron-scale ceramic particles bonded in metal adhesives to form reinforced grinding balls by pouring cast metal penetration to ensure that the ceramic particles are completely embedded in the metal matrix. , and improve structural robustness through sintering and thermal isostatic pressing steps.
It improves the wear resistance and impact resistance of the grinding ball, extends the service life of the grinding ball, reduces manufacturing costs, and has a safe and reliable process.
Smart Images

Figure CN119183412A_ABST
Abstract
Description
Technical Field
[0001] The present invention discloses a metal matrix composite grinding ball obtained by conventional casting technology and reinforced with a preformed shell of a ceramic openwork structure. The shell is a preform placed in the cavity of the casting mold before pouring the cast metal matrix, and the obtained grinding ball has improved resistance to combined abrasion and impact stress.
[0002] The hollow reinforcement structure of the grinding ball disclosed in the present invention is obtained by additive manufacturing in a 3D printer and is composed of microporous aggregates of ceramic metal composite materials and metal particles. The ceramic metal composite particles contain bonded micron-sized particles (particles) of borides, nitrides, carbonitrides or carbides such as TiC, TiCN, NbC, TaC, ZrC, HfC, Mo2C, WC, preferably titanium carbide or titanium carbonitride bonded in a metal binder matrix. During the casting operation, the micropores of the aggregate are infiltrated by the casting metal, and the aggregated ceramic metal composite particles are finally completely embedded in the casting metal matrix. Background Art
[0003] The present invention relates to grinding balls used in drum mills in the grinding and crushing industry, such as cement plants or ore grinding in mines. Grinding balls are subjected to high mechanical stresses and high surface wear due to abrasion or corrosion in bulk. Therefore, it is desirable that the grinding balls should exhibit high abrasion and corrosion resistance, as well as a certain ductility in order to be able to withstand ball-to-ball impacts or ball-to-liner impacts.
[0004] In view of the difficulty in matching these two properties with the same material composition, composite grinding balls have been proposed in the past, which have a matrix made of a relatively ductile alloy in which ceramic particles with good wear resistance are embedded.
[0005] Document CN106914620A (2017) discloses a method for preparing a composite grinding ball, which uses selective laser cladding combined with three-dimensional digital modeling technology, adopts a preform hollow structure, and is placed in a mold cavity before casting.
[0006] Documents CN103357854 (2013) and CN113564511A (2021) disclose ceramic-reinforced grinding balls, wherein the reinforcing layer comprises embedded nano-scale ceramic particles on the surface and sub-surface of the grinding balls. The inner wall of the casting mold is coated with nano-ceramic particles.
[0007] Document WO2022 / 122393 (Magotteaux 2022) discloses a hierarchical composite wear-resistant part reinforced by a triple periodic minimum surface ceramic lattice structure, having a plurality of cell units, the ceramic lattice structure being embedded in a bicontinuous structure having a cast metal matrix. The document does not disclose a hollow ceramic structure of aggregated ceramic-metal composite particles embedded in a cast metal matrix, the ceramic-metal composite particles comprising micron-sized ceramic particles bonded in a binder metal matrix.
[0008] The grinding ball market is cost-sensitive and therefore must target the best levels of wear resistance and price, making the manufacturing process critical. Therefore, the robustness of the prefabricated ceramic spherical hollow structures during the casting operation and their ability to be penetrated by the cast metal without damage are crucial in an economical and safe way of manufacturing them by 3D additive manufacturing.
[0009] Micron-sized ceramic fine powders other than oxides (e.g., TiC, TiCN, NbC, TaC, WC) may be difficult to handle if their size is below 53 μm because they are reactive (potentially flammable and / or explosive) and therefore require an inert atmosphere for safe use in additive manufacturing. On the other hand, larger-sized (>100 μm) non-oxide ceramic particles can be used without a controlled atmosphere, but the performance of such large particles is poor because ceramic particles have a well-known inherent brittleness. Pure ceramic coarse particles of additively manufactured preforms are too brittle to withstand abrasive conditions. From a manufacturing point of view, fine particles are generally difficult to flow, while coarse particles have much higher fluidity. Coarse particles also cause fewer health issues than fine particles. Purpose of the Invention
[0010] The present invention aims to provide grinding balls obtained by conventional casting techniques and reinforced with a shell, the shell being a prefabricated ceramic hollow structure placed in the cavity of a casting mold before casting the grinding balls. The hollow structure contains a suitable concentration of ceramic-metal composite particles embedded in a casting metal matrix and substantially free of unfilled micropores. Summary of the invention
[0011] The invention discloses a composite grinding ball, which comprises: - Ferroalloy metal matrix, - a reinforced shell of a hollow ceramic structure of aggregated ceramic-metal composite particles comprising micron-sized ceramic particles bonded in a binder metal matrix; wherein the aggregated ceramic-metal composite particles are embedded in the ferrous alloy metal matrix.
[0012] Preferred embodiments of the present invention disclose at least one or a suitable combination of the following features: - the micron-sized ceramic particles are selected from metal borides, metal nitrides, metal carbides and metal carbonitrides; - the micron-sized ceramic particles are selected from titanium carbide, titanium carbonitride, niobium carbide, tantalum carbide, zirconium carbide, hafnium carbide, vanadium carbide, molybdenum carbide and tungsten carbide or mixtures thereof; - the micron-sized ceramic particles are selected from titanium carbide or titanium carbonitride or a mixture thereof; - The average particle size D of the ceramic composite particles 50 Less than 500 μm, preferably less than 400 μm; - Average particle size D of micron-sized ceramic particles bonded in the binder metal matrix 50 Less than 30 μm, preferably less than 20 μm, most preferably less than 10 μm; - the binder metal matrix bonding the micron-sized ceramic particles is selected from the group consisting of iron-manganese-based alloys, iron-chromium-based alloys and nickel-based alloys, and wherein the binder metal matrix and the iron alloy metal matrix have different compositions; - the cast ferroalloy metal matrix comprises steel or chromium cast iron; - the concentration of ceramic particles in the hollow structure is 30 to 55% by volume, preferably 35 to 50% by volume; The openings of the reinforcement shell of the hollow ceramic structure account for 10 to 70%, preferably 25 to 70%, of the surface of the grinding ball.
[0013] The present invention also discloses a method for manufacturing the grinding ball of the present invention, which comprises the following steps: -a) additively manufacturing a shell of a ceramic hollow structure using a powder mixture containing ceramic-metal composite particles; -b) placing the shell of the ceramic hollow structure in the cavity of the mold; -c) pouring the ferroalloy cast metal into a mold to obtain the reinforced grinding ball of claim 1.
[0014] Preferred embodiments of the method of the present invention disclose at least one of the following features or a suitable combination thereof: - an additional step of at least partially sintering the shell of the ceramic hollow structure; - the step of at least partially sintering the shell of the ceramic hollow structure comprises: partially impregnating the interstices between the ceramic-metal composite particles of the structure with a metal selected from steel and chromium cast iron or a combination thereof before placing the structure in a cavity of a mold and finally casting it; - a step of at least partial sintering followed by a step of hot isostatic pressing or post-infiltration; - step a) comprises adding 2 to 20 wt. %, preferably 5 to 20 wt. %, most preferably 10 to 18 wt. % of carbide-forming metal particles selected from tungsten, vanadium, molybdenum, titanium, niobium, hafnium and zirconium, or mixtures thereof; - the ceramic composite particles of the powder mixture of step a) comprise at least 95%, preferably 98%, of particles larger than 150 μm. - performing step a) by adhesive jetting technology followed by adhesive curing at a temperature above 100°C; - The step of pouring the cast metal to obtain the reinforced grinding balls is carried out in a grinding ball cluster mould. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 and Figure 2 Various 3D models of prefabricated ceramic hollow structural shells that can be manufactured by additive manufacturing technology and placed into the cavity of a casting mold before pouring are shown.
[0016] Figure 3 and Figure 4 Examples of additively manufactured prefabricated ceramic hollow structure shells are shown, which are single or double spheres containing aggregated ceramic-metal composite particles. The spheres have a diameter of 80 mm and holes of 2 mm diameter.
[0017] Figure 5 Shown is the placement of a prefabricated hollow structural shell in a mold cavity prior to pouring of the cast metal.
[0018] Figure 6 A typical configuration of a mould for grinding balls cast in a cluster mould is schematically shown.
[0019] Figures 7 to 10 3D models of prefabricated ceramic hollow structures of Examples 1 to 4 are shown to illustrate the enhanced grinding balls of the present disclosure. Specifically, (not considering inflow holes): - Figure 7 The hollow structure of the grinding ball of Example 1 with a diameter of 80 mm is shown, having holes / openings with a diameter of 6 mm. - Figure 8 The hollow structure of the 90 mm diameter grinding ball of Example 2 is shown, having holes / openings of 8 mm diameter. - Fig. 9 The hollow structure of the 70 mm diameter grinding ball of Example 3 is shown, having holes / openings of 6 mm diameter. - Fig.10 The hollow structure of the 70 mm diameter grinding ball of Example 4 is shown, having holes / openings of 10 mm diameter.
[0020] Fig.11 The hollow structures of Examples 1 to 4 are presented in a group in true-to-scale form.
[0021] Fig.12 A prefabricated hollow structure is shown in a casting mold. In the following description, the expressions "holes" or "openings" in the hollow structure can be used interchangeably. DETAILED DESCRIPTION Description of the additive manufacturing steps for the hollow structural shell
[0022] In order to manufacture the prefabricated hollow structure disclosed in the present invention, it is necessary to create a digital 3D model structure and construct the structure using powder and metal particles of a ceramic-metal composite material in a 3D printing (additive manufacturing) device. The technology used in this case is preferably binder jetting, but is not limited to this.
[0023] An overview of 3D printing technology and various ASTM standards related to characterization and methods has been published on ScienceDirect: http: / / www.sciencedirect.com / topics / engineering / binder-jetting. This overview summarizes the contents of several papers related to 3D printing technology, which represent the knowledge of those skilled in the art. For the purpose of providing general information, this publication is incorporated herein by reference.
[0024] Binder jetting technology is disclosed in particular in documents US 6,036,777 (2000) and US 2015 / 0069649 A1.
[0025] A complete review of the relevant parameters of binder jetting technology for ceramics is given in a recent publication: “Binder Jetting for Ceramic: Powders, Binders, Printing Parameters, Equipment, and Post-Processing” (2019), Xinyuan Lv, Fang Ye, LaifeiCheng*, Shangwu Fan, Yongsheng Liu, Laboratory of Thermo-Structural Composites Science and Technology, Northwestern Polytechnical University, Xi’an, 710072, China.
[0026] This publication studies the steps and applications of binder jet printing of ceramics and discusses key factors such as powder properties, binders, printing parameters, equipment and post-processing processes as well as the influence of particle shape and size distribution of ceramic powders. The influence of additives such as the droplet formation mechanism and droplet penetration dynamics of the binder are also described. In addition, the document discusses printing parameters such as layer thickness, saturation, printing direction, equipment and post-processing. This paper is incorporated into this application by reference for the purpose of explaining the binder jetting technology.
[0027] An important element of binder jetting technology is the selection of an appropriate type of binder, taking into account its compatibility with the relevant ceramic, ceramic-metal composite or metal powder. Many prior art documents have investigated different types of binders and ceramic powders.
[0028] WO2020 / 146452A1 discloses a specific amine-containing adhesive polymer and a method for additively manufacturing an object by binder jetting. The method comprises feeding a powder for manufacturing the object and a solution containing an adhesive polymer dissolved in a solvent into an additive manufacturing device, respectively, wherein the adhesive polymer is an amine-containing polymer having a molecular weight of at least 200 g / mole, and dispensing selectively positioned droplets of the adhesive polymer from a print head of the additive manufacturing device into a powder bed to bind particles and produce a preform of the object to be manufactured.
[0029] US2019 / 0111618A1 discloses a method for indirectly additively manufacturing an object, by feeding a powder for manufacturing the object and a bifunctional curable monomer or a viscous polymer binder into an additive manufacturing device, respectively, and distributing selectively positioned droplets of the bifunctional curable monomer or the viscous polymer binder from the print head of the additive manufacturing device into a bed of the powder so as to bond the particles of the powder to the bifunctional curable monomer or the viscous polymer binder, thereby producing a curable preform having the shape of the object to be manufactured; and, in the case of a bifunctional curable monomer, curing the curable preform to form a cross-linked object. These documents list a series of available curable monomers and their curing temperatures. The document is incorporated herein by reference. A method for producing a grinding ball according to the present invention.
[0030] The preferred way to manufacture grinding balls reinforced with ceramic metal hollow structure shells is to create a digital 3D model structure (see Figure 1 and Figure 2 , showing various possibilities) and built in a 3D printing device, optionally partially sintering the structure to improve its solidity. The 3D model is then placed in a cluster sand mold, followed by a step of pouring a hot liquid matrix metal (e.g. a high chromium cast iron or steel containing more than 11% chromium by weight) in order to penetrate the micropores of the preform and obtain a grinding ball with substantially no unfilled micropores in its reinforced ceramic-metal composite structure. The manufacturing of the prefabricated hollow structure includes the following steps:
[0031] Digital 3D model structure - Generate a numerical 3D model of the hollow structural shell using computer-aided design (CAD) software (e.g., nTopology) https: / / ntopology.com / generative-design-software / ) and convert it into a format processable by a 3D printing device, such as STL (stereolithography) format. In nTopology, you can use Field-Driven Design to spatially vary the parameters of the hollow structure, such as shell thickness, mesh size, or the geometry of the hollow structure. -The file is then processed by slicing software to slice the model into printable 2D layers with a predetermined thickness.
[0032] Additive Manufacturing (AM) Process The handling of small particles (<100 μm) is often hazardous due to health and / or safety reasons, so larger ceramic-metal composite particles are used in the additive manufacturing process of the present invention, where the fine ceramic particles are bound in a metal binder matrix. - In this process, ceramic metal powder is fed through a hopper and a single layer is built up at a time, the thickness of which is, for example, about 200 to 500 μm, depending on the powder particle size. The ceramic metal powder particles can be selected from nitrides, borides or carbonitrides, such as TiC, TiCN, NbC, TaC, WC, ZrC, HfC, VC, Mo2C, preferably titanium carbide or titanium carbonitride, which is bound in a metal binder matrix and some other carbide-forming metal particles may be present to enhance the wettability of the casting alloy to the ceramic metal composite particles while forming additional carbides in situ. The average particle size (D 50 ) is typically between 200 and 500 μm, preferably between 200 and 400 μm, most preferably between 200 and 300 μm (measured by dry sieving according to ISO 4497:2020). - If the powder granulometry does not meet the particle size distribution target, a sieving step may be required to eliminate the particle size fraction below 150 μm (for safety, flowability or printing resolution reasons). - Ceramic-metal composite powders, possibly associated with metal powders, are introduced into a 3D printing device to build hollow structures deposited layer by layer in a build box (vibration and recoating rollers can be used to increase the packing density of the layers, mainly in the case of fine or poorly flowing powders). -Depending on the additive manufacturing technology, the moving head can produce powder agglomeration in specific areas on the layer, for example by binder jetting. Agglomeration also occurs in the previous layer below the current layer. In the case of binder jetting, a liquid binder is deposited in the form of droplets by a moving head in specific areas of the layer according to the 2D file. An important parameter is to define a suitable saturation level in order to achieve a suitable bond between the particles of the layer and between the previously printed layers. Preferred binders are, for example, water-dispersible glycol acrylic binders, such as tetraethylene glycol dimethacrylate, tetraethylene glycol diacrylate, triethylene glycol dimethacrylate, diethylene glycol 2, methoxyethanol, or preferably a mixture suitable for forming an interconnected molecular network, which can be dispersed in water and cured at 130 to 200°C for about 2 hours per centimeter of material thickness of the box to be cured. -The next layer is then deposited and the above steps are repeated until the entire embedding is built in the powder bed.
[0033] Curing and optional sintering - If a cross-linkable monomer binder is chosen, curing is required. The entire box is heated in a curing oven at a temperature of about 130 to 200°C for a certain period of time (e.g. about 2 hours per cm thickness) depending on the box volume and the printed material in order to provide strength to the part (by polymerization, cross-linking, solvent evaporation or some other mechanism) to ensure temperature uniformity. - The box is then allowed to cool completely and excess powder is removed from the box by, for example, brushing, suction or blowing with compressed air. The green part can be handled safely without risk of breakage. If the green preformed hollow body needs to be sintered, it is placed in a furnace and heated to high temperature (usually above 900°C) under a controlled atmosphere (usually argon or vacuum) to perform the sintering step. The sintering rate to be achieved depends on the desired mechanical properties and final porosity of the hollow structure.
[0034] Grinding ball manufacturing - Place the prepared preform (shell of hollow structure) into the preformed cavity of the cluster sand mold. -The mold is closed and liquid metal is poured into the mold. - It was observed that the gaps of the aggregated ceramic-metal composite powders were generally between 10 and 700 μm, while most of the gaps were between 50 and 500 μm, and the average gap size was between 150 and 300 μm. - The 3D hollow structure has uniform open porosity over the entire volume and, in the case of a partially sintered shell of a ceramic hollow structure, the liquid cast metal penetrates into the remaining microporosity of the structure, resulting in a very tight ceramic / metal bond. - Allow the liquid metal to cool until the grinding balls are completely solidified. The sand mold is then removed and the residual sand on the grinding balls is cleaned, and the conventional casting finishing process steps known to those skilled in the art can be followed (knockout, shot peening, grinding, additional heat treatments such as annealing, quenching, tempering, ...).
[0035] Examples of grinding balls This example is intended to illustrate the present disclosure but should not be considered limiting. Preparation of ceramic-metal composite particles The following powders of TiC, titanium carbonitride, WC, NbC, Mo2C, iron, manganese, chromium and nickel were used for 3 different types of ceramic metal composite particles (CMP 1 to 3), all powders having a particle size less than 325 mesh (<44 μm). Table 1 Composition (weight %) CMP 1 CMP 2 CMP 3 TiC 45 85 <![CDATA[TiC 0.5 N 0.5 ]]> 65 WC 11 Nb 5 <![CDATA[Mo2C]]> 4 Fe 42.6 11.6 Mn 9.1 Cr 2.5 Ni 2.2 0.6 15.0 Mo 1.1 0.3 • The composition of CMP 1 is particularly suitable for impact resistance because it has a relatively low content of ceramic particles (45 wt% TiC) bonded in a tough manganese steel binder. The composition of CMP 2 is particularly suitable for wear resistance because it has a high content of titanium carbide (85 wt. % TiC) bonded in a hard high chromium white cast iron wear resistant binder. The composition of CMP 3 is particularly suitable for corrosion and wear resistance because it has a high content of complex mixture of ceramic particles (TiC 0.5 N 0.5 + WC + NbC + Mo2C = 85 wt% in total), finely tuned to be bonded in a corrosion resistant nickel binder.
[0036] Other ceramic particles may be added to create complex solid solution particles, controlling or fine-tuning the grain size, morphology and / or core-rim structure of the ceramic particles.
[0037] The powder according to the composition of Table 1 was mixed with isopropanol and metal grinding balls in a ball mill and ground for 24 hours to achieve an average particle size D of about 3 μm. 50 .
[0038] An organic wax binder (2% by weight of the powder) is added and mixed with the obtained powder in the grinding step. Alcohol is removed by a vacuum dryer with a rotating blade (the alcohol is condensed for reuse). The agglomerated powder obtained is then sieved through a 600 μm sieve. A tape with a 60% theoretical density of a ceramic / metal powder mixture is manufactured by compacting between the rotating rollers of a roller granulator. The tape is then broken into irregular particles by forcing it to pass through a sieve with an appropriate mesh size. After crushing, the granules are sieved to obtain a size between about 200 and 600 μm. Subsequently, these irregular porous particles are subjected to high temperature sintering (1300-1500° C. for about 2 hours) in a high vacuum furnace with a low argon partial pressure until a minimum porosity (<5% by volume, preferably less than 3% by volume, even more preferably less than 1% by volume) is reached. After sintering, further crushing and final sieving steps are generally required to deagglomerate the ceramic-metal composite particles that may have agglomerated during sintering. Preparation of powder blends for 3D printing :
[0039] The composition and size distribution of the powder blend are influenced by the permeability of the AM shell of the hollow preform structure. This permeability depends mainly on the following parameters: -Thickness and porosity of the hollow preform; - the proportion of the openings in the hollow structure; - The composition of the alloy to be poured into the mould, which will influence the possible overheating required based on the liquidus temperature, the liquidus-solidus range (at the same temperature, high chromium casting alloys penetrate the hollow preform structure more easily than steels...).
[0040] In the past, it has been demonstrated that some metals, such as magnesium, titanium or niobium, have a positive effect on the wettability of the cast metal matrix to the ceramic particles and thus on the permeability of the hollow structural shell. Some of these metals, such as Ti, Nb and other carbide-forming metals, also have a positive effect of combining with the carbon present in the cast iron to form additional carbides, as described below.
[0041] The wettability of ceramic metal particles has been extensively studied by Massoud Malaki et al. in “Wettability in Metal Matrix Composites” (2021) and Banerji et al. in “Role of wettability in the preparation of metal-matrix composites” (1984).
[0042] In the present disclosure, the metallic particles of titanium and niobium play a dual role, as they improve the permeability of the hollow structure and they react with the carbon always present in the iron casting alloy to form additional carbides in situ.
[0043] Ceramic-metal composite particles CMP 1 to 3 were combined with titanium and niobium powders to prepare three different types of powder blends 1 to 3. All powders contained less than 5% by weight, preferably 2% by weight, of particles with a size below 150 μm. The blend according to the table below was mixed in a mixer for 15 minutes. Blends Blend 1 Blend 2 Blend 3 Ceramic Metal Particles (CMP) (wt%) 80 wt% CMP1 93 wt% CMP2 85 wt% CMP3 Titanium particles (wt%) 20 7 Niobium particles (wt%) 15 <![CDATA[D 50 Ceramic metal particles (μm)]]> 220 280 300 <![CDATA[D 50 Titanium particles (μm)]]> 220 220 <![CDATA[D 50 Niobium particles (μm)]]> 250 Casting Alloy weight% C Cr other Fe Casting Alloy 1 2.2 16.5 <2 margin Casting Alloy 2 2.85 14.5 <2 margin Casting Alloy 3 2.3 29 <2 margin
[0044] Casting alloy 1 contains 2.2 wt% C and 16.5 wt% Cr, which is particularly suitable for impact conditions and has appropriate heat treatment to improve impact resistance. Powder of blend 1 was used to make hollow structures. Composite grinding balls of the invention were placed in the same ball mill together with reference metal grinding balls of casting alloy 1 for comparison, processing the same ore for the same period of time under significant impact conditions. Both grinding balls were subjected to the same heat treatment.
[0045] Casting alloy 2 contains 2.85 wt% C and 14.5 wt% Cr, which is particularly suitable for abrasive conditions and has appropriate heat treatment to improve wear resistance. The powder of blend 2 was used to make the shell. The composite balls of the invention and reference metal balls of cast alloy 2 were compared in the same ball mill under significantly abrasive conditions using copper ore.
[0046] Casting alloy 3 contains 2.3 wt% C and 29 wt% Cr, which is particularly suitable for highly corrosive conditions. The powder of blend 3 was used to make the shell. The composite balls of the invention were compared with reference metal balls of cast alloy 3 in the same ball mill under significantly corrosive conditions using magnetite iron ore.
[0047] Depending on the specific properties and the targeted heat treatment, casting alloys 1, 2 and 3 also contain <2 wt. % of other alloying elements known to those skilled in the art (Si, Mn, Mo, Ni, . . . ). Example 1 (Blend 1+Casting Alloy 1) Blend 1 was used to print a ceramic hollow structure shell on an EXone X25 Pro 3D Binder jet printer with a shell diameter of 80 mm, a shell thickness of about 5 mm, and an opening / hole diameter of 6 mm, resulting in a surface coverage of 57% (e.g. Figure 7The part was printed using an aqueous binder based on a mixture of diethylene glycol dispersed in an aqueous solution of 2-butoxyethanol (Aquafuse BA005 EXone).
[0048] The key parameters of AM process are as follows: -The thickness of each printed layer is about 300 μm; -Printing speed is 60 seconds per layer; - 30% binder saturation of the powder pores; and - The powder bulk density is about 43%.
[0049] After completion, the entire printed box is cured in an oven at about 200°C for 2 hours per centimeter of part height, with the dwell time depending on the structure, as multiple objects can be made in one run. After cooling, the printed box is powder-free by suction and brushing to obtain a hollow structure green body.
[0050] The obtained hollow prefabricated structure green body was placed in a furnace and heated to about 1100° C. for 2 hours in a high vacuum.
[0051] The shell of the hollow prefabricated structure contains a total of about 83 volume % of empty spaces available for iron alloy infiltration (about 61 volume % is attributed to the holes / openings of the hollow structure, and another 22 volume % is micron-sized pores), and the remaining 17 volume % of the hollow structure is ceramic-metal composite particles + titanium metal particles.
[0052] The obtained hollow prefabricated structure is then placed in the cavity of a cluster sand mould.
[0053] Hot liquid high chromium white cast iron (having the composition of casting alloy 1) was then poured into the mold, filling 61 volume % of the hollow prefabricated structure due to the openings and penetrating the micrometer-sized pores between the particles of the aggregated structure (22 volume %), while additional carbides were formed by the reaction of the carbon contained in the casting alloy with the metal powder.
[0054] After casting, 39% by volume of the reinforcement volume (1% by volume of the pores of the hollow structure) contained a high concentration of titanium carbide of about 30% by volume. Thus, the total volume content of titanium carbide particles in the reinforcement of the grinding ball was about 12% by volume. Example 2 (Blend 2+Casting Alloy 2) Example 2 was carried out in the same manner as Example 1, but using Blend 2 and a different ceramic hollow structure shell with a shell diameter of 90 mm, a shell thickness of 8 mm, and an opening / hole diameter of 8 mm, resulting in a surface coverage of 69%, such as Figure 8 shown.
[0055] A homogenous powder mixture of Blend 2 was used to print a ceramic hollow structural shell, using the same equipment and printer settings as in Example 1. An aqueous binder based on a mixture of diethylene glycol dispersed in an aqueous solution of 2-butoxyethanol was used to print the part (Aquafuse BA005EXone).
[0056] The key parameters of the AM process are the same as those in Example 1. The obtained hollow ceramic prefabricated structural shell green body is placed in a furnace and heated to about 1000° C. for 2 hours under an argon atmosphere.
[0057] The structure was again obtained with a powder packing density of 46%, which contained a total of about 74 volume % of empty spaces available for iron alloy infiltration (about 42 volume % was attributed to the openings in the structure, and another 32 volume % was the micron-sized pores between the ceramic-metal composite particles), and the remaining 27 volume % of the hollow structure was the structure of ceramic metal and metallic titanium.
[0058] The obtained ceramic hollow structure shell is then placed in the cavity of the sand mold.
[0059] Hot liquid high chromium white cast iron (having the composition of Casting Alloy 2) was then poured into the mold, filling 42 volume % of the openings / voids of the hollow structure and infiltrating 32 volume % of the micrometer-sized pores between the ceramic-metal composite particles of the structure.
[0060] After casting, 58% by volume of the reinforcement volume contained a high content of titanium carbide of about 42% by volume. Thus, the total volume content of titanium carbide particles in the grinding ball reinforcement was about 25% by volume. Example 3 (Blend 3+Casting Alloy 3)
[0061] Example 3 was carried out using Blend 3 and a different hollow structure shell with a shell diameter of 70 mm, a shell thickness of 3 mm, and an opening / hole diameter of 6 mm, resulting in a surface coverage of 64%, as shown in FIG. Fig. 9 shown. The parts were printed using an alcohol binder (Cleanfuse EXone). The key parameters of AM process are as follows: -The thickness of each printed layer is about 450 μm; -Printing speed is 45 seconds per layer; - 35% binder saturation of the powder pores; and - The bulk density of the powder is about 47%.
[0062] The key parameters of the AM process were the same as in the previous example (curing at 200 °C for 2 hours followed by heating in a furnace at 1050 °C for 2 hours in an argon atmosphere).
[0063] The ceramic hollow structure shell is obtained by a powder packing density of 47%, and contains a total of about 77 volume % of empty spaces that can be used for iron alloy infiltration (about 51 volume % is attributed to the openings / holes of the hollow structure, and another 26 volume % is the micron-sized pores inside the structure), and the remaining 23 volume % is the structure of the ceramic metal composite particles + metal niobium particles of the hollow structure.
[0064] The resulting structure was then placed in the cavity of a sand mold, and hot liquid high chromium white cast iron (having the composition of Casting Alloy 3) was then poured into the mold, filling 51 volume % of the openings / pores of the hollow structure and penetrating 26 volume % of the micrometer-sized pores between the particles present in the hollow structure.
[0065] After casting, 49% by volume of the reinforcement volume contains a high content of ceramic particles, such as titanium carbonitride, tungsten carbide, molybdenum carbide and niobium carbide or mixtures thereof or even mixed carbides, such as (Ti, Nb, W, Mo) C, about 43% by volume. Thus, the total volume content of ceramic particles in the reinforcement of the grinding ball is about 21% by volume. Example 4 (Blend 3 + Casting Alloy 2)
[0066] Example 4 was carried out using blend 3 and a different hollow structure shell with a shell diameter of 70 mm, a shell thickness of 3 mm, and an opening diameter of 10 mm, resulting in a surface coverage of 56%, as shown in FIG. Fig.10 shown. Parts were printed using alcohol binder I (Cleanfuse EXone). The key parameters of AM process are as follows: -The thickness of each printed layer is about 450 μm; -Printing speed is 45 seconds per layer; - 35% binder saturation of the powder pores; and - The bulk density of the powder is about 47%.
[0067] The key parameters of the AM process were the same as in the previous example (curing at 200 °C for 2 hours followed by heating in a furnace at 1150 °C for 2 hours in an argon atmosphere).
[0068] The ceramic hollow structure shell is obtained by a powder packing density of 47%, and contains a total of about 77 volume % of empty spaces that can be used for iron alloy infiltration (about 51 volume % is attributed to the openings of the hollow structure, and another 26 volume % is the micron-sized pores inside the structure), and the remaining 23 volume % of the hollow structure is ceramic metal composite particles + metal niobium particles.
[0069] The resulting structure was then placed in the cavity of a sand mold, and hot liquid high chromium white cast iron (having the composition of casting alloy 3) was then poured into the mold, filling 50 volume % of the pores of the hollow structure and infiltrating 31 volume % of the micrometer-sized pores between the ceramic-metal composite particles of the hollow structure.
[0070] After pouring, the 49% by volume reinforcement volume contains about 43% by volume of a high concentration of ceramic particles, such as titanium carbonitride, tungsten carbide, molybdenum carbide and niobium carbide or mixtures thereof or even mixed carbides, such as (Ti, Nb, W, Mo) C. Thus, the total volume content of carbides or carbonitrides in the reinforcement of the grinding ball is about 21% by volume.
[0071] Table 1 The terms "shell", "reinforced shell", "openwork shell" and "openwork" are used interchangeably. The shell thickness is the thickness of the openwork ignoring the pores. Calculated performance indicators compared with conventional grinding balls
[0072] An overview of grinding media testing is given in the article "Overview of grinding media consumption incomminution" (Slabbert, Paton, Moema and Zimba) presented at the World Gold Congress.
[0073] Practical testing of grinding balls on industrial grinding machines is particularly difficult to manage due to the low proportion of test grinding balls relative to the loading of conventional grinding balls. Since the grinding machine contains grinding balls in different stages of wear and with a large diameter size distribution (e.g., diameters from 20 to 70 mm), the test sample usually accounts for less than 0.1% (400 balls out of 400,000 to 800,000 balls). The main difficulty here is that after several days or weeks of grinding, at least a significant number of the composite grinding balls under test and the reference metal grinding balls need to be found among thousands of conventional grinding balls in order to be able to measure a representative average weight loss percentage of the composite test balls for comparison with the reference metal grinding balls.
[0074] A way to solve this problem is to use grinding balls that are slightly larger (about 10 mm larger) than those that are regularly added and already present in the conventional grinder. For example, if the diameter of the fresh conventional grinding balls regularly added to the industrial grinder is 60 mm, the diameter of the test grinding balls (composite grinding balls and reference grinding balls) is selected to be 70 mm in diameter in order to make it easier to retrieve the marked balls. Since these balls are larger, they are not only easier to find visually, but they also have a natural tendency to "float" on the surface of the conventional grinding load.
[0075] The evaluation of the wear performance of the disclosed grinding balls was carried out in the actual case of grinding of copper ore, magnetite iron ore and platinum ore in 3 types of mills A, B, C (having the following characteristics and conditions):
[0076] Grinding of copper ore using grinding balls (diameter 90 mm) of Example 2 - Mill A with a diameter of 7.31 m and a length of 10.97 m, - Contains 660 tons of conventional grinding balls (33% volume filling) - Several tons of conventional grinding balls with a diameter of 76 mm are added regularly every day to compensate for wear -Speed is 11.9 rpm - Traction power is 10500kW -Processing 950 tons of copper ore per hour -use Abrasion condition -Test duration: 8 days
[0077] The magnetite iron ore was ground using the grinding balls of Example 3 and then tested using the grinding balls of Example 4. (70mm) - Mill B with a diameter of 4.6 m and a length of 6.7 m, -Filled with 165 tons of conventional grinding balls (35% volume fill) - Several tons of conventional grinding balls with a diameter of 60 mm are added regularly every day to compensate for wear -Speed 15.1rpm - Traction power is 2300kW -Processing 420 tons of magnetite iron ore per hour -use corrosion condition -Test duration: 20 days
[0078] Grinding of platinum ore in the presence of grinding balls (80 mm) of Example 1 - Mill C with a diameter of 7.925 m and a length of 11.735 m, -Filled with 800 tons of conventional grinding balls (32% volume filling) - Several tons of conventional grinding balls with a diameter of 70 mm are added regularly every day to compensate for wear - Speed between 10.5 and 11.5 rpm - Traction power is 15000kW -Processing 1,000 tons of platinum ore per hour -use Shock condition -Test duration: 10 days Preparation of test samples
[0079] For the performance testing of the composite grinding balls of Examples 1 to 4, and for the metal reference ball type, 200 grinding balls were produced for each example and each grinding ball of the same alloy and reinforcement was marked with the same identification means (e.g., all grinding balls of Example 1 had one or two holes drilled in a defined diameter and position; all grinding balls of Example 2 had 2 holes, etc.). All grinding balls of the same composition were further processed or ground to have the same weight (+ / -2 kg for grinding balls with a diameter of 80 mm) with a tolerance of + / -5 grams, preferably + / -2 grams. The composite grinding balls of the present disclosure and the reference metal grinding balls were made of the same iron alloy and subjected to the same heat treatment so that the effect of the ceramic reinforcement could be evaluated as the only variable.
[0080] In the next step, 200 composite test grinding balls were loaded into industrial mills together with 200 reference metal grinding balls (composite balls of Example 1 were loaded into Mill C, composite balls of Example 2 were loaded into Mill A, composite balls of Example 3 were loaded into Mill B). The above industrial mills already contained their usual conventional grinding ball loads, with a filling rate of about 35% by volume. This means that there are 660 tons of conventional grinding balls for Mill A, 165 tons for Mill B, and 800 tons for Mill C, while the number of test and reference grinding balls (200 test grinding balls and 200 reference balls in each mill) is only 600 to 900 kg, so the effect on the grinding capacity is negligible. Therefore, the addition of the test grinding balls has no significant effect on the overall mill filling.
[0081] The mill then needs to be run for a sufficiently long period of time to observe sufficient wear that can be measured. Under 24 hour / day conditions, the required period of time is typically on the order of several days or weeks.
[0082] Depending on the type of ore to be ground, the wear of conventional grinding balls for magnetite iron ore is known to be about 0.5 mm / 100 hours in diameter (about 2.4 mm after 20 days), while for copper ore, about 1.5 mm / 100 hours in diameter is observed (about 3 mm after 8 days). For platinum ore, the wear is expected to be about 1.3 mm / 100 hours (about 3 mm after 10 days). Considering this indicator related to the wear rate of conventional grinding balls, the test duration was chosen to ensure that the wear is maintained within the thickness of the reinforcing shell, so as to properly interpret the effect of the reinforcing shell itself.
[0083] Finally, the mill was stopped and the found and identified test grinding balls (usually less than 10% of the starting number) were weighed to evaluate the average mass loss and calculate the performance index, as shown in the results table below. Performance index calculation
[0084] For each example of grinding balls, the average weight loss was measured before and after the test duration, and the average weight loss percentage was calculated. Weight loss% / 100=(initial weight-final weight) / initial weight The performance indicators are defined as follows: The weight loss of the reference material is the average weight loss of the reference metal grinding balls. PI = weight loss of reference metal grinding balls / weight loss of test composite grinding balls
[0085] A performance index above 1 means that the test composite grinding ball of the invention has less wear than the reference, and below 1 means that the test composite grinding ball has more wear than the reference. The reference grinding ball is a conventional grinding ball made of the same cast alloy but without any ceramic reinforcement. As shown in the table below, the grinding balls of the present invention have better performance on average due to the reinforced shell.
[0086] The performance indicators of Example 3 show that the composite shell performs best with smaller diameter pores compared to the larger pores of Example 4. Examples 1 to 4 show that composite core-shell grinding balls with different particle properties and compositions, casting alloys, and testing conditions perform significantly better.
[0087] The performance of the composite grinding balls disclosed herein is compared to the conventional grinding balls described above. As long as the reinforcement shell is not completely worn and completely lost, the thickness of the reinforcement shell naturally has an impact on the overall performance of the grinding balls. A grinding ball with a composite reinforcement shell thickness of 10 mm will have better long-term performance than a grinding ball with a reinforcement shell thickness of 5 mm. Impact of performance indicators on overall grinding performance
[0088] The following table compares the wear (expressed as average weight loss percentage) of Examples 1 to 4 (composite grinding balls) with their respective reference grinding balls. The increased life was calculated taking into account their performance indicators and their influence on the life of the grinding balls.
[0089] The life of the grinding balls is usually evaluated by the time required for the grinding balls to wear from their initial diameter to 20 mm. Once the diameter of the grinding balls reaches 20 mm, they are considered small enough to leave the mill through the outlet trunnion together with the ground material. The measured weight loss is converted into a diameter reduction per unit time, allowing the increased lifespan to be calculated.
[0090] Due to the reinforcing hollow structure, a significant lifetime increase is observed, whereby the diameter of the grinding balls remains close to its initial value for a longer period of time.
[0091] Examples 1 to 4 show significantly better performance of composite core-shell grinding balls having different particle compositions and properties, casting alloys, and testing conditions. Observations
[0092] Regardless of the effects of various ceramic metal and cast alloy compositions on wear behavior in a specific grinding environment, the effect of the geometry of the hollow structures disclosed herein plays an important role. Parameters to be considered are, for example, the surface coverage of the ceramic reinforcement, the opening size, the ratio of the thickness to the opening size, and the distance between the openings (see Table 1).
[0093] It was observed that the ease with which cast iron alloys penetrated the hollow structures was generally inversely proportional to the surface coverage and thickness of the reinforcement, and directly proportional to the size of the openings and the distance between the openings. However, the wear resistance of a particular CMP / cast alloy composition depended on the surface coverage and thickness of the reinforcement, and was inversely proportional to the size of the openings and the distance between the openings.
[0094] Since the difficulty of permeability should not be underestimated, a compromise must be found between these parameters, bearing in mind that a high hollowing thickness (>10 mm) combined with very small openings (<2 mm) far apart should be avoided, while a lower hollowing thickness (<10 mm) with medium openings (>2 mm) close to each other (<10 mm) should be preferred. Advantages of the present invention
[0095] Compared with conventional grinding balls, the present invention has the following advantages: Better wear efficiency due to better wear resistance of the cover layer which occupies most of the wearable volume (having reinforcement everywhere in the ball is futile) The composite grinding balls can be provided with improved wear resistance and / or mechanical properties by adjusting the nature, size and volume content of the ceramic particles and using an appropriate metal binder matrix for the ceramic-metal composite particles, such as combining a high mechanical properties manganese steel with an appropriate iron casting alloy (e.g., high chromium white cast iron for wear resistant parts), wherein the binder metal matrix may be different and complementary to the cast iron alloy metal matrix. Better wear and / or mechanical properties of the grinding balls due to controlled porosity and / or crack defects in the particles before casting. Easy / simple craft.
Claims
1. A composite grinding ball, comprising: - Ferroalloy metal matrix, - a reinforced shell of a hollow ceramic structure of aggregated ceramic-metal composite particles comprising micron-sized ceramic particles bonded in a binder metal matrix; wherein the aggregated ceramic-metal composite particles are embedded in the ferrous alloy metal matrix.
2. The composite grinding ball according to claim 1, wherein the micron-sized ceramic particles are selected from the group consisting of metal borides, metal nitrides, metal carbides and metal carbonitrides.
3. The composite grinding ball according to claim 1 or 2, wherein the micron-sized ceramic particles are selected from titanium carbide, titanium carbonitride, niobium carbide, tantalum carbide, zirconium carbide, hafnium carbide, vanadium carbide, molybdenum carbide and tungsten carbide or mixtures thereof.
4. The composite grinding ball according to any one of the preceding claims, wherein the micron-sized ceramic particles are selected from titanium carbide or titanium carbonitride or mixtures thereof.
5. The composite grinding ball according to any one of the preceding claims, wherein the average particle size D of the ceramic composite particles is 50 Less than 500 μm, preferably less than 400 μm.
6. The composite grinding ball according to any one of the preceding claims, wherein the average particle size D of the micron-sized ceramic particles bonded in the binder metal matrix is 50 Below 30 μm, preferably below 20 μm, most preferably below 10 μm.
7. The composite grinding ball according to any one of the preceding claims, wherein the binder metal matrix to which the micron-sized ceramic particles are bonded is selected from the group consisting of iron-manganese based alloys, iron-chromium based alloys and nickel based alloys, and wherein the binder metal matrix and the iron alloy metal matrix have different compositions.
8. The composite grinding ball according to any one of the preceding claims, wherein the cast ferrous alloy metal matrix comprises steel or chromium cast iron.
9. The composite grinding ball according to any one of the preceding claims, wherein the content of ceramic particles in the hollow structure is 30 to 55% by volume, preferably 35 to 50% by volume.
10. The composite grinding ball according to any one of the preceding claims, wherein the aggregated ceramic-metal composite particles comprise sintered metal, the sintered metal filling the gaps between the hollow structured ceramic-metal composite particles, the sintered metal being selected from steel and cast iron or a combination thereof.
11. The composite grinding ball according to any one of the preceding claims, wherein the openings of the reinforcement shell of the hollow ceramic structure occupy 10% to 80%, preferably 20% to 70%, most preferably 25% to 65% of the grinding ball surface.
12. The method for manufacturing a composite grinding ball according to claims 1 to 11, comprising the following steps: -a) additively manufacturing a shell of a ceramic hollow structure using a powder mixture containing ceramic-metal composite particles; -b) placing the shell of the ceramic hollow structure in the cavity of the mold; -c) pouring the ferroalloy cast metal into a mold to obtain the reinforced grinding ball of claim 1.
13. The method according to claim 12, comprising the additional step of at least partially sintering the ceramic hollow structure.
14. The method of claim 13, wherein the step of at least partially sintering the shell of the ceramic hollow structure comprises: The interstices between the ceramic-metal composite particles of the structure are partially impregnated with a metal selected from steel and chrome cast iron or a combination thereof before the structure is placed in a mold cavity and finally cast.
15. The method according to claims 13 to 14, wherein the step of at least partially sintering the shell of the ceramic hollow structure is followed by a hot isostatic pressing step or a post-infiltration.
16. The method according to claim 12, wherein step a) comprises adding 2 to 20 wt. %, preferably 5 to 20 wt. %, most preferably 10 to 18 wt. % of carbide-forming metal particles selected from tungsten, vanadium, molybdenum, titanium, niobium, hafnium and zirconium, or mixtures thereof.
17. The method according to claim 12, wherein the ceramic composite particles of the powder mixture of step a) comprise at least 95%, preferably 98%, of particles larger than 150 μm.
18. The method of claim 12, wherein step a) is performed by a binder jetting technique followed by binder curing at a temperature above 100°C.
19. The method of claim 12, wherein the step of pouring the cast metal to obtain the reinforced grinding balls is performed in a grinding ball cluster mold.
